INCLUSIVE EDUCATION IN FINLAND HIGHER SCHOOLS (EDUCATION IN THE 21ST CENTURY, 2024)
For a long time in various countries around the world, a diversified approach to people with disabilities (PWD) has been used, leading to their isolation and perceived as discrimination. However, at the beginning of the 21st century, an inclusive approach began to be applied, aiming for the full integration of PWD into society. Despite the widespread adoption of the inclusive approach in Europe, including Finland, in countries like Armenia, its implementation remains declarative. Within the framework of the study, Finland's experience was analyzed with the aim of applying it in Armenia to improve the effectiveness of inclusive higher education. The study's conclusions emphasize that the issue of disability is not only a medical but also a social problem that requires ensuring the full integration of PWD into society. This implies the development of support programs that take into account both physical and socio-psychological aspects. The main areas of practical support for students with disabilities have been identified, including interaction, instructional materials, and the environment. These concepts can be implemented in state programs in Armenia aimed at supporting inclusive education and students with disabilities.
Keywords: persons with disabilities; inclusive approach; inclusive education; Finnish education system; concept of equal rights; accessibility of higher education